Experimental Study on the Permeability of Weakly Cemented Rock under Different Stress States in Triaxial Compression Tests. (23rd October 2018) - Fan, Gangwei; Chen, Mingwei; Zhang, Dongsheng; Wang, Zhen; Zhang, Shizhong; Zhang, Chengguo; Li, Qizhen; Cao, Bobo
Abstract : Mudstone and shaly coarse sandstone samples of Jurassic units in northwestern China were collected to study the seepage mechanism of weakly cemented rock affected by underground mining operations. Samples were studied using seepage experiments under triaxial compression considering two processes: complete stress-strain and postpeak loading and unloading. The results show that permeability variations closely correspond to deviatoric stress-axial strain during the process of complete stress-strain. The initial permeability is 7 times its minimum, contrasting with lesser differentials of initial, peak, and residual permeability. The magnitude of permeability ranges from 10 −17 to 10 −19 m 2, representing a stable water-resisting property, and is 1 to 2 orders lower in mudstone than that in shaly coarse sandstone, indicating that the water-resisting property of the mudstone is much better than that of the shaly coarse sandstone. Permeability is negatively correlated with the confining pressure. In response to this pressure, the permeability change in mudstone is faster than that in shaly coarse sandstone during the process of postpeak loading and unloading. Weakly cemented rock has lower permeability according to the comparison with congeneric ordinary rocks. This distinction is more remarkable in terms of the initial permeability. Analyses based on scanning electron microscope (SEM) observations and mineral composition indicate that the samples are rich in clay minerals such as montmorillonite and kaolin, whose inherent properties of hydroexpansiveness and hydrosliming can be considered the dominant factors contributing to the seepage properties of weakly cemented rock with low permeability.